Planificación tributaria de la empresa VASCONEZIMPORT CIA. LTDA. del cantón Riobamba del período 2014, para establecer controles tributarios. - Gavilanes Picón, Ivonne Katerine. (2016)
With the aim of analyzing the impact of the Tax Planning since it is considered to be a set of legitimate on the part of the taxpayer or taxpayer actions, which aims to manage and invest the resources within the business so that the lowest possible tax burden generated establishing Tax Controls that would make the dependent variable in this study, so, official data of the Constitution of the Company, interviews and questionnaires with the Administration were studied to obtain relevant information in the Tax Field, which allowed to make tables and graphs that made possible the analyzes of the constant tax benefits on what is stipulated in the Constitution of the Republic, the Organic Law of the Internal Taxation, Tax Code, the Organic Code of Production and others.